Artificial Intelligence and Human Autonomy in Education: The Search for Equilibrium - Stephen , Onyekachi Chukwu; Nathaniel , Terna Igbangi; Ahmed , Sadiq (Kashere Journal of Education, 2025)
Artificial Intelligence (AI) is being celebrated as solution to human inadequacies in almost every sector of human society. In education, the impact of AI is significant. However, in the bid to efficiently assist in achieving educational objectives, concerns are raised to the fact that AI is interfering with human autonomy. The aim of this paper, therefore, is to develop working strategies for achieving equilibrium between artificial intelligence and human autonomy in education. Using analytic philosophy as a tool, the paper discussed in depth the concepts of artificial intelligence and human autonomy. It highlighted critical areas in education where AI is having a sphere of dominance and the prospects it brings to education. Nonetheless, the paper concedes to the fact that human autonomy faces great challenges in education because of undefined AI boundaries. The paper proposes some strategies to effectively guide the use of AI and to ensure that those traditional areas of human interaction in education are protected.